Determinants of Insurance Awareness and Perceived Value and Their Impact on Unit Linked Insurance Customer Retention With The COVID-19 Pandemic as Moderator - Japari Antony; Hermana Budi; Sudaryanto Sudaryanto (Journal of Social Science, 2023)
Purpose – During the covid 19 pandemic life insurance companies faced matter of concerning to extension of customers of unit linked insurance policies. Unit-linked life insurance product has become a major contributor to the company's profits. This study aims to investigate the factors that influence insurance awareness and perceived value and their impact on customer retention with the covid 19 pandemic as a moderator. Design/methodology/approach – This study conducted an online survey and total of 230 completed questionnaires were collected from customers in Jakarta. The data was analyzed using SmartPLS software. Findings – Results indicate that insurance awareness, perceived value, and covid 19 pandemic significantly influence customer retention. Insurance agents, psychological factors and financial literacy significantly influence insurance awareness. E-service quality significantly affects perceived value. The interaction between the covid 19 pandemic and insurance awareness and the interaction between the covid 19 pandemic and perceived value did not significantly affect customer retention. Originality/value – The study contributes to the marketing literature by proposing a conceptual model: the life insurance customer retention model. The findings offer practical guidance to life insurance companies to keep the customer loyalty.